BESEDOTVORJE PRASLOVANSKEGA GLAGOLA V PRIMERJALNOJEZIKOSLOVNI LUČI (Philological Studies, 2019)
In the article the word formation of Proto-Slavic verb is discussed from comparative-linguistic prospective. Word-formationally motivated verbal classes with typical infinitve suffixes (PSl. *-nǫ-, *-ě 1/’a-, *-i-, *-a-, *-ov/’ev-a-) are compared with their parallels in other (ancient) Indo-European languages. On the basis of this external comparison the word-formational patterns of Proto-Slavic verb are grouped, according to their geographical distribution within Indo-European branches, in terms of relative chronology (Late-Proto-Indo-European, NonCommon-Indo-European, Proto-Balto-Slavic, Proto-Slavic).